A Compact Design of 4×4 Butler Matrix with Four Linear Array Antenna at 38 GHz - Rahayu, Yusnita; Simanihuruk, J. R. M; Yuyu Wahyu (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2022)
This paper creates a compact design of a 4×4 butler matrix integrated with an array of antenna elements at 38 GHz frequency. The antenna simulation performance is acceptable, approaching the ideal one. The butler matrix can generate four beams through the output port directly. Each input port 1, 2, 3, and 4 has beam direction, which is 42°, -19°, 19°, and -42°, respectively. The phase difference between output ports of the butler matrix is approaching 45° and 135°. Besides, antenna patch simulation has a good performance. The results are still acceptable after combining the butler matrix and four linear array antenna.